Peningkatan Mutu Layanan Prima di Madrasah Melalui Siklus PDCA dan Analisis SERVQUAL - Eko Rubiyantoro; Nurfuadi Nurfuadi (Ikatan Dai Indonesia, 2026)
This research is motivated by the shift in the paradigm of Islamic education in the era of global competition, where madrasas are required to transform into professional service provider institutions capable of providing excellent service. The main focus of this study is to analyze the managerial role of the Madrasa Head in improving service quality through the integration of the Plan, Do, Check, Act (PDCA) cycle and the Service Quality (SERVQUAL) instrument. The writing method used is a literature study with descriptive qualitative analysis. The discussion results show that the implementation of managerial functions through the PDCA cycle provides a systematic framework for the Madrasa Head to plan, implement, evaluate, and improve service standards continuously. The use of the SERVQUAL instrument is proven effective as an objective measurement tool to identify the gap between stakeholder expectations and service reality across five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The integration of these two approaches creates a dynamic quality management ecosystem where modern values such as professionalism are synergized with Islamic values such as Ihsan (excellence) and Itqan (professionalism). This paper concludes that the PDCA-SERVQUAL synergy is capable of creating a competitive advantage for madrasas, shifting leadership patterns to be data-driven, and ensuring that educational services remain relevant to the demands of the times without losing their Islamic identity.